Factor Models for Portofolio Credit Risk - Philipp J. Schönbucher (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
This paper gives a simple introduction to portfolio credit risk models of the factor model type. In factor models, the dependence between the individual defaults is driven by a small number of systematic factors. When conditioning on the realisation of these factors the defaults become independent. This allows to combine a large degree of analytical tractability in the model with a realistic dependency structure.
Keywords: G13; 330; Default Risk; Portfolio Models